Investigation of Crossbars with Reinforced Concrete and Composite Reinforcement - Umarov Shodiljon Abdug ‘ofurovich (Research Parks Publishing LLC, 2023)
This article presents an analysis of the results of research work on the study of composite reinforcement elements, widely used at present in the restoration of concrete structures in buildings and structures under construction in the Republic of Uzbekistan and abroad.